Initial and severe cases of influenza in 2020-2022 and population immunity prior to epidemic season - N. P. Kolosova; T. N. Ilyicheva; S. V. Svyatchenko; A. V. Danilenko; G. S. Onkhonova; K. I. Ivanova; I. M. Susloparov; A. B. Ryzhikov (Медицинская иммунология, 2022)
The purpose of the present work was to evaluate population immunity to influenza and molecular genetic analysis of influenza viruses detected in the Russian Federation over 2020-2022. In this study, 1344 samples of blood serum collected prior to the 2021-2022 flu season in Siberian, Southern, Far Eastern, Volga and Ural Federal Districts were studied. Seropositivity to the A/Victoria/2570/2019 vaccine strain (H1N1) pdm09 was detected in 25% to 31% of samples from the four federal districts, and in 8% of samples from the Far Eastern Federal District. Seropositivity to the A/Cambodia/e0826360/2020 strain (H3N2) was detected in 24% to 37% of the samples. The lowest population immunity was revealed to the influenza B/Washington/02/2019 vaccine strain (Victoria lineage), with < 10% of serum samples reactive to the studied strain. Since March 2020, the worldwide turnover of all seasonal respiratory viruses has sharply decreased, except of rhinoviruses. From March 2020 to June 2021, we have identified six B/Victoria influenza viruses from sporadic cases of influenza. From June 2021 to the end February 2022, the State Research Center “Vector” received 901 samples positive for influenza A(H3N2) virus RNA, two specimens positive for A(H1N1) pdm09 virus RNA, and 17 samples positive for influenza B. All studied A(H3N2) viruses belonged to the 3C.2a1b.2a2 subclade (Bangladesh group). The two verified A(H1N1) pdm09 influenza viruses belonged to the 6B.1A.5a clade. All studied influenza B viruses were assigned to the B/Victoria genetic lineage, and to 1A.3a2 subclade. The genomes of all identified viruses did not contain mutations of the NA gene responsible for drug resistance to neuraminidase inhibitors, or mutations in РA gene responsible for baloxavir resistance. All viruses tested by fluorescence assay were sensitive to oseltamivir and zanamivir. The worldwide frequency of influenza isolates resistant to antineuraminidase drugs does not exceed 1-2% of cases. Hence, oseltamivir and zanamivir provide effective treatment for seasonal influenza.